Housing boom-bust cycles and asymmetric macroprudential policy - William Gatt (Central Bank of Malta, 2018)
Macroprudential policy is pre-emptive, aimed at preventing crises. Empirical evidence hints at the existence of asymmetric policy in booms and recessions. This paper uses a New Keynesian model with a financial friction on mortgage borrowing and collateral to show what implications this asymmetry might have on the economy. The main source of fluctuations is a bubble in the housing market, which causes house prices and credit to deviate from their fundamental values, leading to a boom and bust cycle. The main macroprudential tool is the regulatory loan to value (LTV) ratio. The author finds that while the asymmetric policy dampens the boom phase, it introduces more volatility in the economy by exacerbating the correction that follows. The higher the asymmetry in the policy response, the more volatile the economy is relative to one in which policy reacts symmetrically.
Keywords: C61; E32; E44; E61; R21; 330